The mediating role of perceived enjoyment among the relationship between psychological and social mobilizers and attitude toward activities sports in Iraq - Haider H. Jawad; Reem Abdulkareem Shuit; Taha Al-Haili; Tawfeeq Alghazali; Qasim Khlaif Kadhim; Ahmed Abdulateef Sabti; Hassan Naji Mahmood, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Youth is passionate about sports, and they want to win. The performance of the players is crucial to the team's success. The members of the team with mental and social issues function less effectively. As a result of their problems, the professionalism of the Iraqi footballers has declined. This study seeks to determine the role of perceived enjoyment as a mediator between psychological and social mobilizers and attitudes toward sports activities in Iraq. This study is predicated on the quantitative data acquired from Iraqi players from various teams. 800 questionnaires were issued for data collection, and the response rate was fifty percent. This study's findings are determined using the PLS structural and measurement models. This study aimed to improve Iraqi athletes' attitudes toward sporting activities. The study concludes that perceived enjoyment influences the relationship between psychological and social mobilizers and attitudes toward sports activities. The addition of the current model to the body of knowledge is substantial. This report also includes highly suggested recommendations for increasing players' performance in Iraq by fostering a good attitude about the game.